A CRITICAL REVIEW ON THE CONCEPT OF DRUG AS A WHOLE - Tatapudi, Mahesh Babu; Ravi Kumar, Ch.; Vijayalakshmi, A.; Narasimha, V. (International Journal of Ayurveda and Pharma Research, 2017)
Drug is an independent variable and one among Pada Chatustaya. Successful treatment depends on the choice of appropriate dose and dosage form. Nowadays the advancement in science has led to the extensive use of extracts and isolated compounds. Principles of extraction are seen in the classical dosage forms where a suitable homogenous medium was used based on the type of the drug. Drugs having water-soluble fraction are used as Kwatha, those having fat-soluble fractions are used as Ghrita/ Taila and so on. Present day extracts are obtained by extracting herbal drug of certain particle size with suitable extraction medium. Ayurveda propounds the principles of Rasa Panchaka and attributes the actions of a drug to any one of the Rasa-Vipaka-Guna-Veerya-Prabhava where each component plays a specific role or a combined role. Hence a chemically isolated derivative may not serve the purpose and will produce adverse effects. Even-though drugs have got some active principles with which they work, they have some other fractions too, which counteract their bad effects, if any. Therefore Ayurveda advocates that drug should be used as a whole so that the desired effects may have without any side effects. Therefore, research works should be directed towards providing the use of whole drugs and find ways to potentiate the drugs as per principles of Ayurveda. This article highlights the importance of administration of drug as a whole rather than extracts or isolated phytochemicals.